2018
DOI: 10.3390/ijerph15102116
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Justice, Burnout, and Engagement in University Students: A Comparison between Stressful Aspects of Labour and University Organisation

Abstract: Burnout, engagement, and organisational justice concepts are usually studied in the context of labour organisations, but not in universities. For this, the objective of this research is to identify the students’ empirically evidenced relationships in the employment context, such as levels of organisational justice, stress indicators, burnout and work commitment. On the other hand, engagement is analysed as a mediating variable that explains the relationship between organisational justice and burnout. A sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…The classical study of Jahoda et al (1933) showed that prolonged unemployment affects the social aspects of an employee’s whole life unfavorably. Topical research has predicted many of the adverse outcomes of unemployment on young people, among them, financial distress, depression, decreased life satisfaction ( Lorenzini and Giugni, 2010 ; Navarro-Abal et al, 2018 ), and poor psychological outlook ( Amissah and Nyarko, 2017 ; Åslund et al, 2014 ; Crowe and Butterworth, 2016 ; Paul and Moser, 2009 ). Detailed review has revealed conclusive evidence of this from different fields: medicine and psychology, for instance.…”
Section: Discussionmentioning
confidence: 99%
“…The classical study of Jahoda et al (1933) showed that prolonged unemployment affects the social aspects of an employee’s whole life unfavorably. Topical research has predicted many of the adverse outcomes of unemployment on young people, among them, financial distress, depression, decreased life satisfaction ( Lorenzini and Giugni, 2010 ; Navarro-Abal et al, 2018 ), and poor psychological outlook ( Amissah and Nyarko, 2017 ; Åslund et al, 2014 ; Crowe and Butterworth, 2016 ; Paul and Moser, 2009 ). Detailed review has revealed conclusive evidence of this from different fields: medicine and psychology, for instance.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we could not adjust for a full set of potential confounders, such as company size, industrial category, detailed work duties, corporate social responsibility, or organizational justice, all of which may affect work engagement. 40,41 These are important areas for examination in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Academic burnout has been related to low levels of academic engagement and academic self-efficacy [ 16 ], poor academic performance [ 17 ] and low levels of personal well-being and academic happiness, factors that may lead to school failure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%